Persistent solar wind forcing of the F2-region ionosphere observed at Tromsø - Borries, Claudia (2024)
The state of the high-latitude thermosphere-ionosphere system gets modified by the solar wind passing Earth. The modifications are best visible during storm conditions. During these conditions, large amounts of solar wind energy are ingested into the thermosphere-ionosphere system which cause global changes in thermosphere and ionospheric electron density. This study investigates 22 years of Total Electron Content (TEC) and 15 years of ionosonde data (critical frequency foF2 and height of maximum electron density hmF2) at Tromsø (70°N, 19°E) with a correlation analysis. The ionosphere parameters are correlated with different solar wind parameters observed at the Lagrangean Point L1. The results show that the ionospheric parameters systematically respond with an increase or decrease depending on local time, season and solar cycle. During winter night conditions TEC and foF2 increase with solar wind energy and during summer daytime they decrease with increasing solar wind energy. The summer negative ionospheric response is more intense during solar maximum conditions, while the winter positive ionospheric response is stronger during solar minimum. Cross polar cap plasma convection, particle precipitation and Joule heating are considered to be the main drivers of the electron density changes at Tromsø. Local time, season and solar cycle changes in the background ionosphere-thermosphere conditions lead to different effects of theses driving processes.